Effects of film mulching on the physiological and morphological parameters and yield of cucumber under insufficient drip irrigation. (7th April 2022) - Yan, Haofang; Ma, Jiamin; Zhang, Jianyun; Wang, Guoqing; Zhang, Chuan; Akhlaq, Muhammad; Huang, Song; Yu, Jianjun
Abstract: A comprehensive study was conducted to analyse the influence of film mulching on the soil water content (SWC), plant physiological and morphological parameters, yield and irrigation water use efficiency (IWUE) of cucumber grown in a greenhouse. The experiment was designed to set the film mulching (M1) and non‐film mulching (M0) applications under two irrigation levels (T1: sufficient irrigation; T2: insufficient irrigation). Thus, four treatments, i.e. T1M1, T1M0, T2M1 and T2M0 were set. The response of plant growth, physiology characteristics, yield and SWC under the designed treatments was analysed based on the data from two planting years (2019 and 2020). Applying film mulching effectively improved the SWC by approximately 10%. The cucumber plant height, stem diameter and leaf area index (LAI) under the T2M1 treatment increased by 38.0–63.1, 16.5–24.9 and 84.0–89.4%, respectively, compared to the T2M0 treatment. The maximum yield was found in the T1M1 treatment, which increased by 24.2–27.5% compared to T1M0. Film mulching increased cucumber yield by 18.0–24.7% compared to non‐film mulching. It was also observed that film mulching under insufficient drip irrigation had a positive influence on plant morphological parameters (photosynthetic rate and stomatal conductance). Among the four treatments, the maximum photosynthetic rate (= 20.69 μmol m −2 s −1 ) and stomatal conductance (= 0.47 μmol m −2 s −1 ) were found in the T2M1 treatment. The sap flow rate under the T2M1 treatment was close to that under the T1M0 treatment, while the largest variation in the sap flow rate occurred under the T1M1 treatment, and the smallest variation occurred under the T2M0 treatment. It can be concluded that the effect of the film mulching technique on cucumber yield and IWUE was significant under insufficient drip irrigation. Résumé: Une étude complète a été menée pour analyser les influences du paillage en film sur la teneur en eau du sol (SWC), les paramètres physiologiques et morphologiques des plantes, le rendement et l'efficacité de l'utilisation de l'eau d'irrigation (IWUE) du concombre cultivé en serre. L'expérience a été conçue pour placer les applications de paillage en film (M1) et de paillage sans film (M0) sous deux niveaux d'irrigation (T1: irrigation suffisante; T2: irrigation insuffisante). Ainsi, quatre traitements, à savoir T1M1, T1M0, T2M1 et T2M0, ont été définis. La réponse de la croissance végétale, des caractéristiques physiologiques, du rendement et du SWC dans le cadre des traitements conçus a été analysée à partir des données reçues pour deux années de plantation (2019 et 2020). L'application du paillage en film a amélioré efficacement le SWC d'environ 10%. La hauteur, le diamètre des tiges et l'indice foliaire (LAI) du concombre sous le traitement T2M1 ont augmenté de 38.0 à 63.1%, 16.5 à 24.9% et de 84.4 à 89.4% respectivement par rapport au traitement T2M0. Le rendement maximal a été obtenu au traitement T1M1, qui a été augmenté de 24.2 à 27.5% par rapport à T1M0. Par rapport au paillage sans film, le rendement en concombre a augmenté de 18.0 à 24.7%. On a également observé que le paillage en film dans le cadre de l'irrigation goutte à goutte insuffisante a exercé un impact positif sur les paramètres morphologiques des plantes (taux de photosynthèse et conductance stomatique). Parmi les quatre traitements, le taux maximal de photosynthèse (= 20.69 μmol m‐2 s‐1) et la conductance stomatique (= 0.47 μmol m‐2 s‐1) ont été obtenus au traitement T2M1. Le débit de sève en traitement T2M1 est proche du traitement T1M0, tandis que la variation la plus importante du débit de sève est donnée par le traitement T1M1 et que la variation la plus faible est observée dans le traitement T2M0. On peut en conclure que la technique du paillage en film a eu un effet significatif sur le rendement et la valeur des concombres lorsque l'irrigation goutte à goutte était insuffisante.